Retail investors perspectives towards equity investment decision on innovative business - MS. B. NEERAJA; MR. V. DHILIP (The journal of contemporary issues in business and government, 2020)
The aim of this research is on perspective of retail investors towards equity investment decisions in this report its deal with how an individual or retail investor view of perspective towards equity investment.Each and every person perspective is different that will based on the situation the investor been through, education status, experience of investors towards stock, there financial positions, families, friends, relationships and lot more will be directly influenced the individual or retail investors perspectives towards the equity investment. But the thing is their perspective may be different based on lot situations but the main motivation or intention of any type of investor is the same that is to get maximum return of the investment made on the equity of the shares. And this paper helps to understand how the investors, that is the individual investors or retail investors, determine equity based on the need of investors and also their perspective among equity. Also this research report states with shares, stock market, NSE, BSE, SEBI, India economy influenced by stock markets and lot more this paper. This paper concluded with the very basic methodology of stock , share, equity of the individual or retail investors perspective in India.